Diseño del sistema QHSE de la empresa Cinco Ltda - Calderón Charry, Jarrinson; Sanjuán Vega, Eileen Johanna (Escuela Colombiana de Ingeniería Julio Garavito, 2015)
With the present thesis a model of Integrated Management System for the products and services offered by the company CINCO LTDA is shown; as well as the management manual, which includes the documented procedures defined by the organization and the description of the interaction of its processes. The above taking as a basis the requirements regulated in the standards NTC ISO 9001: 2008 Quality Management System, NTC ISO 14001: 2004 Environmental Management System and the NTC OHSAS 18001: 2007 Occupational Health and Safety Management System; with which the procedures and documents of the Integrated Management System were created. The work was structured in three (3) chapters: the first refers to the theoretical framework, the second gives information about the organization and the third details the Integrated System.

Con la presente tesis se muestra un modelo de Sistema de Gestión Integrado para los productos y servicios ofrecidos por la empresa CINCO LTDA; así como también el manual de gestión, en el cual se incluyen los procedimientos documentados definidos por la organización y la descripción de la interacción de sus procesos. Lo anterior tomando como fundamento los requisitos regulados en las normas NTC ISO 9001:2008 Sistema de Gestión de Calidad, NTC ISO 14001:2004 Sistema de Gestión Ambiental y la NTC OHSAS 18001:2007 Sistema de Gestión de Seguridad y Salud Ocupacional; con los cuales se crearon los procedimientos y documentos del Sistema de Gestión Integrado. Se estructuró el trabajo en tres (3) capítulos: el primero se refiere al marco teórico, el segundo da información sobre la organización y el tercero detalla el Sistema Integrado.
Keywords: Calidad; Prevención de riesgos laborales; Medio Ambiente; Sistema de gestión integrado; Modelos de gestión; Integrated Management System; Environmental; Prevention of Occupational Risk; Quality